THE EFFECTIVE FACTORS ON MANAGEMENT DISCUSSION AND ANALYSIS OF FIRMS LISTED ON THE STOCK EXCHANGE OF THAILAND - Promtong, Nantiya; Thiptanamanee, Pattarasiri; Kultangwattana, Worravit (Journal of Liberal Arts and Management Science Kasetsart University, 2024)
This research aims to provide empirical evidence regarding the factors influencing the disclosure of Management Discussion and Analysis (MD&A), which reflects the financial position and operating performance of firms listed on the Stock Exchange of Thailand (SET). The sample group consists of 87 companies registered on the Stock Exchange of Thailand that have participated in preparing MD&A with the Securities and Exchange Commission. Data were collected from annual reports and the Stock Exchange of Thailand website. The data were analyzed using descriptive statistics, including mean, percentage, standard deviation, maximum, and minimum values, as well as inferential statistics, specifically multiple regression analysis. The findings reveal that the shareholder structure, ownership by foreign investors, and the identification of MD&A disclosures in corporate policies and strategies are positively correlated with the degree of MD&A disclosure. The results indicate that businesses with foreign shareholders holding ordinary shares or those seeking international investments should be attentive to augmenting voluntary disclosure, promoting transparency, and ensuring sufficient information disclosure. Explicitly stating MD&A disclosure in corporate policies and strategies can instill confidence, potentially attracting investors to eventually invest in the company.